Implementasi Algoritma Apriori Untuk Sistem Penilaian Kepuasan Mahasiswa Terhadap Pelayanan Di Universitas Hasyim Asy’ari (Studi Kasus di Universitas Hasyim Asy’ari) - Ferdiansa, Ifan; Imam Agung, Achmad; Faizah, Arbiati (Inovate, 2022)
Student satisfaction assessment system is a system that be can used to determine the nature of student related services available the institution based on criteria in service quality. Academic services describe aspects that are superior and are invisible but can be felt by students. Quality academic services will create quality students. Asy'ari Hasyim University, one of the pesantren-based educational institutions is demanded to provide quality academic services. This research aims to improve services at Hasyim Asy'ari University, thereby increasing student satisfaction. In this study applying the Apriori Algorithm in conducting frequent itemset searches with the association rule technique. The writer uses a quantitative approach. Quantitative approach is a method that emphasizes the analysis of numerical data (numbers) obtained by the method itself. With the grouping of data like this, it is expected that the Hasyim Asy'ari University can assess and improve academic services. As well as knowing the relationship between a priori algorithm and student satisfaction with campus services, the level of student satisfaction is known as well as looking for inadequate services Keywords: Algoritmh Apriori, student satisfaction, service quality, quantitative